Pattern of female child mortality among women in raebareli : an explanation through probability model - Pandey, Krishna; Kumar, Pradip; Singh, Ram Dular (International Journal of Health, 2016)
One of the principal determinants of population growth is mortality. The level of female child mortality is often taken as indicator of health conditions, but these may be in general regarded as an indicator of the development of a society and an important indicator of overall development of a country. In this paper, the probability model for number of female child death among women, have been derived. The application of the model in the paper is illustrated through its application to the data from Raebareli district of Uttar Pradesh from Concurrent Assessment of Health & Family Welfare Programs and Technical Support to District of Uttar Pradesh (CATA, 2005-06). The models are estimated on the basis of observed set of data and are tested for their suitability.